Characteristics of thermal energy removal from heat-generating porous media considering liquid-vapour phase change. (February 2020) - Chakravarty, Aranyak; Datta, Priyankan; Ghosh, Koushik; Sen, Swarnendu; Mukhopadhyay, Achintya
Abstract: Heat-generating porous media is encountered in different industrial applications as well as natural processes - natural geysers, geothermal energy extraction, packed bed reactors, nuclear and thermal power plants etc. The present article discusses the characteristics of thermal energy removal from heat-generating porous media, considering phase change of the saturating fluid phases. The complex phenomena of multiphase flow through porous media, coupled with the associated heat and mass transfer processes, is modelled numerically and implemented in a general computational platform with the help of user-defined functions. The model is validated extensively with experimental data and utilised for analysing heat removal from a heat-generating porous bed submerged in a liquid pool. This is in contrast to the various specialised numerical codes that have been specifically developed for modelling these phenomena. The study analyses the fundamental impacts of bed porosity, particle size and bed configuration on heat transfer and multiphase flow mechanism in the heat-generating porous bed. Bed porosity and particle size are observed to influence both fluid transport and heat transfer mechanisms, while bed composition is observed to mainly affect the fluid transport process. These effects, as such, influence heat removal from the heat-generating porous bed, which is quantified in terms of the maximum temperature rise within the bed and the ultimate energy removal possible from the bed. The latter is represented in terms of dryout power density, which represents the minimum volumetric heat generation at which it becomes impossible to ensure adequate heat removal from the bed. Assessment of dryout power density, as such, is very important in the context of heat removal and safety of the related applications. Increase in particle size as well as porosity is observed to augment this limit. The influence of bed composition on this limit is observed to be determined by the interplay of two parameters bed height and interface area of the bed with the surrounding liquid pool.